Knowledge, Attitude, and Behaviours about Covid-19 Prevention between Indonesians and Bangladeshis - Desmawati, Desmawati; Bachtiar, Farah Dina; Fatema, Kanis; Parveen, Shahanaz (Jurnal Keperawatan Soedirman, 2021)
Jakarta-Bogor-Depok-Tangerang-Bekasi (Jabodetabek) is the city with the most populous population in Indonesia. This study aims to explore the knowledge, attitude, and behaviour of Jabodetabek people as an epicentre covid-19 in Indonesia. This study was a descriptive quantitative online study with a survey design used a self-developed online questionnaire on 297 Jabodetabek residents in Indonesia. The chairman of the neighbourhood was encouraged to roll out the google form (link) to as many participants as possible, and then the link was forwarded to the next participants and so on. Data were analyzed using descriptive statistics. Among the participants, 72.1 % were female, overall range of correct answers for knowledge questionnaire was 53.2-97.3%, that for attitude was 21.55-93.3% and for behaviors was 66.3-98.7 %. In general, participants had a good knowledge about the disease, a positive attitude, and behavior towards protective measures. However, the results showed that only 22.55% participants state Indonesian government can win the battle against covid-19, the rest (78.45%) less optimistic attitudes, and this will impact less good practice toward covid-19 in the future, although currently still 66.3% of participants following Government Indonesian policy. Findings of this study revealed that knowledge among people of Jabodetabek about covid-19 is satisfactory. Yet almost half of participants are lacking belief in the plague. Better trust and behavior is required to tackle Covid-19 in Jabodetabek-Indonesia.